2014
DOI: 10.1094/php-rs-12-0160
|View full text |Cite
|
Sign up to set email alerts
|

Four Common Setaria Species are Alternative Hosts for Clavibacter michiganensis subsp. nebraskensis, Causal Agent of Goss's Bacterial Wilt and Blight of Corn

Abstract: Goss's bacterial wilt and blight, caused by Clavibacter michiganensis subsp. nebraskensis (Cmn), has reemerged as an important disease of Zea mays (corn) in the U.S. Midwest. Results from a 2011 multistate survey indicated that Setaria spp. (foxtail) were often present in corn fields with a history of Cmn. The objective of this research was to determine if Setaria spp. that are common in the Midwest are susceptible to infection by Cmn. In the greenhouse, seedlings of four Setaria spp., including S. viridis (gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…drummondii ), and eastern gamagrass ( Tripsacum dactyloides ) are reported to act as secondary hosts for C. nebraskensis (Langemeier et al, 2012 , 2014 ; Schuster, 1975 ; Webster et al, 2019 ). Furthermore, annual ryegrass ( Lolium multiflorum ), bristly foxtail, giant foxtail, green foxtail, yellow foxtail, Johnson grass ( Sorghum halepense ) and large crabgrass ( Digitaria sanguinalis ) have been reported to be hosts of C. nebraskensis based on symptom development in artificially inoculated plants (Ikley et al, 2015 ; Langemeier et al, 2014 ). The pathogen was isolated from barnyard grass ( Echinochloa crus‐galli ) although subsequent experiments failed to confirm that it could be infected (Ikley et al, 2015 ; Wysong et al, 1981 ).…”
Section: Host Range Of the Pathogenmentioning
confidence: 99%
See 1 more Smart Citation
“…drummondii ), and eastern gamagrass ( Tripsacum dactyloides ) are reported to act as secondary hosts for C. nebraskensis (Langemeier et al, 2012 , 2014 ; Schuster, 1975 ; Webster et al, 2019 ). Furthermore, annual ryegrass ( Lolium multiflorum ), bristly foxtail, giant foxtail, green foxtail, yellow foxtail, Johnson grass ( Sorghum halepense ) and large crabgrass ( Digitaria sanguinalis ) have been reported to be hosts of C. nebraskensis based on symptom development in artificially inoculated plants (Ikley et al, 2015 ; Langemeier et al, 2014 ). The pathogen was isolated from barnyard grass ( Echinochloa crus‐galli ) although subsequent experiments failed to confirm that it could be infected (Ikley et al, 2015 ; Wysong et al, 1981 ).…”
Section: Host Range Of the Pathogenmentioning
confidence: 99%
“…Using amplified fragment length polymorphism (AFLP) analysis and repetitive DNA sequence‐based BOX‐PCR, Agarkova et al ( 2011 ) reported 131 C. nebraskensis strains collected between 1969 and 2009 clustered into two groups, A and B, where group B represents recent genetic changes between 1999 and 2009 while the genome of group A had been stable for a long period of time. Similarly, Langemeier et al ( 2012 ) used AFLP and rep‐PCR DNA to separate 466 strains collected in the United States into three main groups. No geographical basis for groupings was noted.…”
Section: Genetic Diversity and Population Structurementioning
confidence: 99%
“…18 The re-emergence of Goss's wilt in the United States has been linked to factors of susceptible hybrids, higher planting populations, less diverse crop rotations, higher residue, reduced or no-tillage practices, longitude, yield history, and growth stage. 19 Glyphosate and surfactant use was also suggested to be a cause of increased plant disease. 20,21 However, follow-up research studies and reviews have indicated that there are no associations between herbicide tolerance traits, glyphosate use, and surfactant use with an increase in plant disease and Goss's wilt.…”
Section: Introductionmentioning
confidence: 99%
“…In severe cases, yield reductions as high as 50% have been reported. Since there is no known effective chemical control for Cn , producers rely on tillage, clean farm equipment, and primarily good corn genetics [ 9 , 14 , 17 , 18 , 19 , 20 , 21 ]. Controlling alternative hosts such as Seteria viridis (green foxtail) may also reduce the Cn transmission to and infection of corn plants [ 17 , 22 ].…”
Section: Introductionmentioning
confidence: 99%